Laminoplasty in Motion: Evolving Techniques and Complications - Singleton, Ian M.; Piple, Amit S.; Crawford, Ben; Mittal, Ashish; Rosinski, Alexander A.; Kondrashov, Dimitriy G. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2023)
Cervical laminoplasty is an increasingly popular surgical option for the treatment of cervical spondylotic myelopathy (CSM) and ossification of the posterior longitudinal ligament (OPLL). Over the past few decades, there have been substantial developments in both surgical technique and hardware options. As the field of cervical surgery rapidly evolves, there is a timely need to reassess the evolving complications associated with newer techniques. This review aims to synthesize the available literature on cervical laminoplasty and associated mechanical complications pertaining to different laminoplasty hinge fixation options.
Keywords: laminoplasty; complications; hardware; open door; double door; cervical spondylotic myelopathy